The Saudi Arabian national demographic and health survey, 2017: Study design and oral health-related influences - Naif Abogazalah; Constantin Yiannoutsos; Esperanza-Angeles Ma; Muhammad Tantawy; Juan Fernando Yepes (Elsevier, 2023)
Objective: To describe the study design, and the distal and proximal influences on oral health reported in the national demographic and health survey (DHS) of the Kingdom of Saudi Arabia (KSA) in 2017. Methods: The 2017 KSA DHS used an innovative multistage stratified random-sampling technique to select the population sample by using primary health care centers' (PHCs) catchment areas as the primary sampling unit. Over 45,000 household heads plus a family member were interviewed. A conceptual framework for distal and proximal oral health influences specific to the KSA was adapted based on the oral health surveillance model. Cross-tabulation and Chi-square tests were performed with consideration for sample weights to provide estimates representative for the KSA population. Frequencies and weighted percentages for each variable reflecting each construct were reported. Results: The total number of individuals included in the analysis was n = 55,511, ages ranging between 2 and > 65 years. Lack of dental care when needed was reported for 22.5 % of the population (males = 20.8 %/females = 24.7 %). Proportion of population from Central, West, East, South, and North regions who reported available dental care services when needed was 62.3 %, 58.0 %, 58.9 %, 62.3 %, and 60.1 %, respectively. PHCs were the most regular source for dental care (55.1 %). In total, 48.3 % visited the dentist at least once last year (males = 49.4 % /females = 46.8 %). Dental pain was the most common reason for last dental visit (69.0 %), while only 6.4 % reported visited the dentist for routine visit. Only 15.3 % reported brushing their teeth at least twice per day (males = 14.6 % /females = 16.4 %). Conclusion: Two major oral health influences previously reported to have a significant negative influence on oral health, namely, limited routine dental check-up visits and inadequate oral hygiene, were present among KSA residents. Further inferential study is needed to investigate such influence on oral health status within the KSA population.